REPORT OF COMMITTEE ON REVISION OF THE STATEMENT OF PRINCIPLES. - Newcomer, Hale L. (The Accounting Review, 1948)
Abstract In October, 1946, President Eric L. Kohler with the then President elect Professor Hermann C. Miller, appointed the Committee on Revision of the Statement of Principles of the American Accounting Association. The appointment of a special committee on revision of the Statement of Principles represented a significant departure from past procedures. As the members of the Association well know, efforts in the past to formulate and summarize accounting principles were those of the Executive Committee of the Association. The Committee undertook first to survey opinion which would aid it, first, in deciding whether a new statement of principles was desirable and, second, if deemed desirable by the Committee, in the formulation of such a statement. It was believed a democratic procedure must offer each member of the Association an opportunity to express himself; that each member must feel he had been given an opportunity to state his position and thoughts. The Committee decided the most economical coverage could be obtained through the medium of the accounting review.